Jurisdição, biodiversidade e sociedade em rede: perspectivando o caso dos ecossistemas manguezal e restinga - Santos, Miriam Cheissele dos (2022)
The year 2020, in addition to being marked by the sad effects of the Covid-19 pandemic, can be identified by the notorious concerns arising from environmental problems, combined with the growing studies that corroborate this scenario, demonstrating an environmental crisis that has been announced for a long time. It is in this scenario that the Judiciary has been provoked to speak out about socio-environmental issues. Inserted in this panorama, this dissertation starts from the concern consolidated in the following problem: to what extent the judicial discussions involving the case of the Mangrove and Restinga ecosystems, in the popular action nº 5067634- 55.2020.4.02.5101 and the allegations of non-compliance with fundamental precept numbers 747, 748 and 749, were they built from the perspective of the constitutionally adequate response and procedural democratization? The phenomenological-hermeneutic approach will be adopted for the investigation, thus, the researcher interacts with her object of study, and from the language/unveiling of the studied phenomena, she suffers the effects of the result, seeking to understand possibilities for the problem. The procedural bias was the bibliographic and documental research and techniques of filing and summary. In addition to the general objective regarding the confrontation of the problem, it seeks to reconstruct how the resonance of State paradigms in the Jurisdiction took place, demonstrating the insufficiency of the dominant paradigm in the face of the emergence of new rights in the Network Society; to investigate the challenges of sociobiodiversity, especially concerning the mangrove and Restinga ecosystems, for Brazilian jurisdiction; defend a constitutionally adequate response to the case of mangroves and sandbanks as a condition of possibility for a democratic jurisdictional process. The path taken until facing the problem, allowed reflections about the performance of the jurisdiction and obstacles in the face of the commitments assumed by the Democratic State of Law, in which there is a displacement of the decisions of the Public Power to the constitutional jurisdiction. Confronting judicial discussions involves understanding that the 1988 Constitution contemplates the fundamental right to an ecologically balanced environment for present and future generations. A Democratic, Social and Ecological State is constituted, adopting the constitutional principles of prohibition of social regression, progressive legal protection of the environment, and democratic participation. These have been violated by the revocation, especially due to the composition of Conama at the time, subtraction of the protection of the 300-meter strip and places of refuge or reproduction of migratory birds, as well as risks for the preservation of water resources. It was concluded that the decision of the Federal Supreme Court, when declaring the unconstitutionality of the act that promoted the revocation, was built from the perspective of the constitutionally adequate response, although, in part, away from procedural democratization. It was understood that the decisions recorded in the records of the popular action illustrate decisions rooted in the dominant paradigm identified in the research, which presents itself as an obstacle. This paradigm prevents the perception of problems that it is no longer able to solve, allied to the education model that contributes to this alienation. The environmental crisis that we are experiencing must serve to think about the limits of a society that supports progress at all costs, in addition to the timeless time in relationships, which supplants the place to propose a uniformity focused on the competition, characteristics of a Network Society and neoliberal. It seeks to contribute to the reflection of principles arising from the commitments of this State that must be assumed by the jurisdiction in the face of socioenvironmental issues.